2019
DOI: 10.1371/journal.pone.0224115
|View full text |Cite
|
Sign up to set email alerts
|

Experienced males recognise and avoid mating with non-virgin females in the western flower thrips

Abstract: The western flower thrips Frankliniella occidentalis (Thysanoptera: Thripidae) is a major insect pest on a wide range of crops throughout the world. There are several unexplained aspects of the mating behaviour, particularly in relation to male-male competition and mate choice. The objectives of the study were to test whether males can detect the mating status of females and whether males avoid mating with previously mated females. Experiments involved either ‘experienced’ adults taken from a laboratory cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Although two components of a male-produced aggregation pheromone, which attracts both males and females, have been identified and investigated with olfactometer experiments 27 , there have been no close-range studies of the mating behaviour. Our pilot observations indicated that there were some distinct and unexpected differences from the behaviour we observed in F. occidentalis 20 , 28 . Males often avoided mating with older virgin females and virgin females often strongly resisted male mating attempts.…”
Section: Introductionmentioning
confidence: 42%
See 2 more Smart Citations
“…Although two components of a male-produced aggregation pheromone, which attracts both males and females, have been identified and investigated with olfactometer experiments 27 , there have been no close-range studies of the mating behaviour. Our pilot observations indicated that there were some distinct and unexpected differences from the behaviour we observed in F. occidentalis 20 , 28 . Males often avoided mating with older virgin females and virgin females often strongly resisted male mating attempts.…”
Section: Introductionmentioning
confidence: 42%
“…In F. occidentalis , females appear to mate with the first male they encounter and then depart 6 , 14 . In laboratory bioassays, females mated readily with most males 20 , which also suggests that females are not choosing. Terry and Dyreson 14 suggested that male F. occidentalis could be competing for the best sites on flowers, where females are more likely to land, which would mean that females do not need to choose because preselection by the males themselves has occurred prior to female visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been noted in the Australian field cricket that male dominance status is associated with the expression of male pheromone signals (Thomas and Simmons, 2009). Akinyemi and Kirk (2019) found that an antiaphrodisiac pheromone was produced in F. occidentalis males but not in females. Thus, as L1 and T lineages have substantial variations genetically and in host adaptations, the type and quantity of male-produced pheromones may be varied too, and it may be the reason behind variations in the intensity of male fighting performance observed.…”
Section: Tablementioning
confidence: 97%
“…Similar as many other herbivorous insects, thrips perceive chemical signals of plant volatiles and insect pheromones using their sensory organs for host recognition, feeding, and other life activities such as mating and oviposition [ 7 , 8 , 9 , 10 , 11 ]. For example, western flower thrips, F. occidentalis can be attracted by stereoisomers, a type of volatiles released by their host plants [ 12 ], and they can also react quickly when perceiving alarm pheromones released by other second-instar nymphs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%